Home Security – Door Lock / Nurulhafizah Shukri - Shukri, Nurulhafizah; Abd Aziz, Nur Fatin Najihah; Mohd Azman, Nurul Husniyah; Ab Mahadi, Mudrikah (2022)
The purpose of this study is to make improvements to the current product that has been proposed which is for door knobs. The improvements are based on the technology for security. Nowadays, the number of burglaries has been a significant challenge for many years around the world. Therefore, our company made a few suggestion ideas for this project to make door knob home security. Before producing this technology product, our company has gone through the process needed in producing a new product. For new product development, the research and development for this product is done with the idea generation, idea screening and market survey in order to produce a good product. Next, the target customers for our product are the homeowner and person who are going to buy a house. This product is good for them to make their house more secure from being break in by burglars. The concept test also has been conducted in order to get the analysis about what our target customers know about door knob home security. The prototype is built to give an overview for the target user on how our product will look like. Lastly, the test marketing also has been conducted to get the information for door lock home security and know the average price that is suitable for our product.